Influence of Nanoclay Addition on the Fatigue Behavior of Polymer Nanocomposites. (2018) - Vijayashakthivel, A.T.; Krishnamurthy, R.; Ravisankar, B.; Karunakaran, C.
Abstract: The addition of nanoparticle with low strength matrix material is a well-known technique to improve the mechanical properties. Several researchers and industrial people have done many works and same has been published in the recent years. But only a limited number of studies have been made focusing on the fatigue behaviour. The objective of this study is to analyse the fatigue behaviour of low density polyethylene (LDPE)/clay nanocomposites with the help of experimental fatigue analysis. LDPE/Montmorillonite nanoclay based composites were prepared by simple melt compounding technique. The nanocomposites were prepared by adding nanoclay of different wt.% in to the LDPE matrix. The nanocomposites were analyzed for nanoclay dispersion by using scanning electron microscope (SEM) and transmission electron microscope (TEM). The prepared nanocomposites were subjected to bending fatigue on the standard specimen. The S-N curves were drawn for different percentage of nanoclay added polymer nanocomposites. The results demonstrated that the fatigue life of the nanocomposites is depending upon the magnitude of stress, dispersion of the clay particle and percentage of nanoparticle as well.